2016
DOI: 10.1186/s12885-016-2231-3
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of miR-21 in regulation of tumor suppressor gene PTEN in human cervical cancer cells

Abstract: BackgroundExpression of the microRNA miR-21 has been found to be altered in almost all types of cancers and it has been classified as an oncogenic microRNA or oncomir. Due to the critical functions of its target proteins in various signaling pathways, miR-21 is an attractive target for genetic and pharmacological modulation in various cancers. Cervical cancer is the second most common cause of death from cancer in women worldwide and persistent HPV infection is the main etiologic agent. This malignancy merits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 64 publications
3
47
0
1
Order By: Relevance
“…Таким обра-зом, было выбрано 18 молекул микроРНК, так назы-ваемых «потенциально маркерных» микроРНК: miR-106 [21,24], miR-1246 [25,26], miR-125b [27][28][29], miR-126 [30][31][32], miR-145 [33,34], miR-146a [35,36], miR-146b [37], miR-155 [38,39], miR-192 [40], miR196b [41], miR-200b [42,43], miR-203 [44,45], miR-20a [46], miR-21 [47,48], miR-31 [49]; miR-34a [27,50]; miR-375 [51,52], miR-99a [53]. Их участие в церви-кальном канцерогенезе было подтверждено как мини-мум в 2 независимых исследованиях.…”
Section: материалы и методыunclassified
“…Таким обра-зом, было выбрано 18 молекул микроРНК, так назы-ваемых «потенциально маркерных» микроРНК: miR-106 [21,24], miR-1246 [25,26], miR-125b [27][28][29], miR-126 [30][31][32], miR-145 [33,34], miR-146a [35,36], miR-146b [37], miR-155 [38,39], miR-192 [40], miR196b [41], miR-200b [42,43], miR-203 [44,45], miR-20a [46], miR-21 [47,48], miR-31 [49]; miR-34a [27,50]; miR-375 [51,52], miR-99a [53]. Их участие в церви-кальном канцерогенезе было подтверждено как мини-мум в 2 независимых исследованиях.…”
Section: материалы и методыunclassified
“…Studies have shown that the abnormal expression of microRNAs (miRNAs) plays an important role in the occurrence, progression, diagnosis, treatment, and prognosis of most tumors, including cervical cancer [3,4]. miRNAs are a type of small non-coding singlestranded RNA that can bind to the 3′-untranslated region (UTR) of target gene mRNA via complementary base pairing, inhibiting the degradation or translation of target gene mRNA, regulating gene expression at the post-transcriptional level, and participating in the regulation of cellular processes, such as inflammatory and stress responses, differentiation, apoptosis, and migration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…26 A recent study identified up-regulation of miR-21 in cervical cancer, which in turn down-regulates the expression of PTEN and promotes cell proliferation and cell survival. 27 Little is known about the expression of miR-135b in cervical cancer. Down-regulation of miR-135b markedly inhibited proliferation and arrested cell cycle in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%